The impact of employees' perceptions about top management engagement on sustainability development efforts and firm performance. (22nd March 2022) - Gopalakrishna‐Remani, Venugopal; Byun, Kyung‐Ah ( Kay); Doty, D. Harold
Abstract: Because sustainability management plays a vital role in firm performance, it is critical to understand the underlying mechanisms that drive better firm performance with sustainability adoption. Thus, drawing upon responsible leadership theory and the dynamic resource‐based view, this study examines how the level of sustainability adoption influences firm performance, both environmental and financial, emphasizing the role of top management beliefs and participation in sustainability adoption. With responses from 310 employees working in manufacturing, healthcare, and retail industries, the SEM analysis results support that (i) perceived top management's strong beliefs lead to a higher level of sustainability adoption by organizations; (ii) perceived top management's active participation positively moderates the relationship between perceived top management beliefs and the level of sustainability adoption; (iii) the higher level of sustainability adoption results in better environmental and financial performance; and (iv) environmental performance positively and partially mediates the relationship between the level of sustainability adoption and financial firm performance. Finally, we offer guidance to managers who would like to leverage top management attributes to achieve environmental and financial performance via environmental sustainability practices.